2017
DOI: 10.14639/0392-100x-1334
|View full text |Cite
|
Sign up to set email alerts
|

Body-worn triaxial accelerometer coherence and reliability related to static posturography in unilateral vestibular failure

Abstract: Poichè le alterazioni della funzione vestibolare possono essere causa di disequilibrio, i principali reperti sviluppati ad oggi per misurare il controllo posturale e l’integrazione sensoriale nel danno vestibolare sono stati ottenuti grazie alla posturografia. Tuttavia, al fine di superare i problemi legati a tale genere di tecnologia, sono stati proposti gli accelerometri indossabili (ACC) come un’alternativa portatile e a basso costo per la misurazione dell’oscillazione corporea in ambienti confortevoli. D’a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Other posturography studies typically used one of the many parameters which could be evaluated to compare the accelerometer and the force plate. For instance, in the Whitney study, the highest correlations were observed for the normalized path length (0.88–0.96 for 6th condition of dynamic posturography), in the Mancini et al study that was the centroidal frequency (0.89) while Alessandrini et al found the correlation coefficients close to 1 for the distance of the COP or COM and the measurements of characteristic frequencies in the power spectral density of the sways 10 , 11 . Such highly sophisticated parameters are usually not a subject in a clinical evaluation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other posturography studies typically used one of the many parameters which could be evaluated to compare the accelerometer and the force plate. For instance, in the Whitney study, the highest correlations were observed for the normalized path length (0.88–0.96 for 6th condition of dynamic posturography), in the Mancini et al study that was the centroidal frequency (0.89) while Alessandrini et al found the correlation coefficients close to 1 for the distance of the COP or COM and the measurements of characteristic frequencies in the power spectral density of the sways 10 , 11 . Such highly sophisticated parameters are usually not a subject in a clinical evaluation.…”
Section: Discussionmentioning
confidence: 92%
“…The main problem was the tensiometer platform and the accelerometers posturography applying different measurement principles, which may interfere with the diagnostic process’ integrity. For people with balance disorders, the reliability of the sensor-based sways recording method was strongly related to measurements on the force plate under static conditions 9 , 11 . However, the differences between the tools may appear to be significant when considering the head movement conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wearables consisted of validated Movit G1 devices (by Captiks, Rome, Italy) 13 , 14 , 22 , 38 with three-axis accelerometer and three-axis gyroscope sensors on-board. The Movit G1 were placed on body segments, by means of Velcro™ strips, in particular on the body back, on each forearm and arm, on each upper and lower leg, on the dorsum of each hand and of each foot, for a total of fourteen sensors (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Low jerk indicates coordinated motion while greater jerk describes more disjointed movements. Jerk was chosen because it is commonly implemented in waist-mounted IMU studies, though it is frequently reported incorrectly with units of m 2 /s 5 [ 5 , 10 , 16 , 35 ]. While the definition for calculating jerk reported by Johnson et al [ 33 ] is accurate, we were unable to find other studies that utilized it for assessing a static balance task.…”
Section: Methodsmentioning
confidence: 99%